Fall Prevention Conceptual Framework. Issue 4 (October 2020) - Abraham, Sam
Abstract : Falls can have lasting psychological and physical consequences, particularly fractures and slow- healing processes, and patients may also lose confidence in walking. Injuries from falls lead to functional decline, institutionalization, higher health care costs, and decreased quality of life. The process related to the problem of patient falls in the hospital, using the nursing model developed by the theorist, Ida Jean Orlando, is explained in this article. The useful tool that provides guidance to marketers in this endeavor is Maslow's hierarchy of needs. During acute illness, individuals are greatly in need of satisfying their physiological needs. If these needs are not met, patients leave the hospital lacking a positive experience. Initial fall risk assessment is critical to plan intervention and individualize care plan. Interventions depend on the severity of fall risk factors.